Ti–5Al–5Mo–5V–3Cr bone implants with dual-scale topography: a promising alternative to Ti–6Al–4V. (23rd March 2020) - Micheletti, Chiara; Lee, Bryan E J; Deering, Joseph; Binkley, Dakota M; Coulson, Simon; Hussanain, Asad; Zurob, Hatem; Grandfield, Kathryn
Abstract: Modifications to the compositional, topographical and morphological aspects of bone implants can lead to improved osseointegration, thus increasing the success of bone implant procedures. This study investigates the creation of dual-scale topography on Ti–5Al–5Mo–5V–3Cr (Ti5553), an alloy not presently used in the biomedical field, and compares it to Ti–6Al–4V (Ti64), the most used Ti alloy for bone implants. Dual-scale surface topography was obtained by combining selective laser melting (SLM) and electrochemical anodization, which resulted in micro- and nanoscale surface features, respectively. Ti5553 and Ti64 samples were manufactured by SLM and showed comparable surface topography. Subsequent electrochemical anodization succeeded in forming titania nanotubes (TNTs) on both alloys, with larger nanotubes obtained with Ti5553 at all investigated anodization voltages. At an anodization voltage of 40 V, a minimum time of 20 min was necessary to have nanotube formation on the surface of either alloy, while only nanopores were evident for shorter times. Seeded Saos-2 cells showed ideal interactions with surface-modified structures, with filopodia extending to both surface microparticles characteristic of SLM and to the interior of TNTs. Attractiveness of Ti5553 lies in its lower elastic modulus ( E  = 72 GPa) compared to Ti64, which should mitigate stress-shielding phenomena in vivo . This, combined with the analogous results obtained in terms of dual-scale surface topography and cell-substrate interaction, could indicate Ti5553 as a promising alternative to the widely-employed Ti64 for bone implant device manufacturing.